2005
DOI: 10.1016/j.ypmed.2005.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Cancer preventive screening: A cross-border comparison of United States and Canadian Chinese women

Abstract: Objective-To compare screening mammography and Pap testing among Chinese women in Seattle, Washington to Vancouver, and British Columbia. Results-Chinese women in Vancouver were younger, more educated and fluent in English. Unadjusted rates of mammography and Pap testing were similar between the two cities. Provider type was consistently associated with screening in both cities; female providers had the highest rates and Chinese male providers the lowest. Adjusted logistic regression analysis demonstrated simi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 42 publications
0
20
1
Order By: Relevance
“…Some researchers also argue that doctors and friends represent the two most significant sources of information on health for Chinese emigrant women [18]. In North America, extensive and tailored educational programs and research to target underserved communities has a major role in reducing health inequalities across ethnic communities [19][20][21]. A randomized controlled trial of interventions to promote cervical cancer screening among Chinese women in North America found that interventions such as culturally and linguistically appropriate outreach and direct mail can enhance cervical screening participation [20].…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers also argue that doctors and friends represent the two most significant sources of information on health for Chinese emigrant women [18]. In North America, extensive and tailored educational programs and research to target underserved communities has a major role in reducing health inequalities across ethnic communities [19][20][21]. A randomized controlled trial of interventions to promote cervical cancer screening among Chinese women in North America found that interventions such as culturally and linguistically appropriate outreach and direct mail can enhance cervical screening participation [20].…”
Section: Discussionmentioning
confidence: 99%
“…Prior research has shown that health care providers can impact their patients' decisions to undergo cancer screening by raising the issue during appointments. 20,21 Electronic reminder systems have been used with success in improving cancer screening and preventive services in ambulatory care clinics, [22][23][24][25] particularly in academic settings. 26 We plan to develop and implement an educational program and an electronic reminder system to improve HBV risk assessment and screening in our academic general medicine clinic.…”
Section: Discussionmentioning
confidence: 99%
“…Pap testing rates are consistently found to be lower among Chinese women than Caucasian women (Yu and Perrine, 1997; Kagawa-Singer and Pourat, 2000; Taylor et al, 2002; Tu et al, 2005), with devastating health consequences. Compared to the general population in North America, Chinese women have a higher incidence of cervical cancer and associated mortality (Archibald et al, 1993; Parkin et al, 1993), and present for treatment at more advanced stages (Jenkins and Kagawa-Singer, 1994).…”
Section: Introductionmentioning
confidence: 99%